European integration from below. The construction of the Ems-Dollart region, 1964–1978 - Molema, Marijn (Journal of European Integration History, 2011)
Keywords: Ems-Dollart-Gebiet; Europäische Integration; Regionalentwicklung

Projekt Nur Mut / gewoonweg durven. Kooperationspartner Regiopolitie Noord en Oost Gelderland / Kreispolizeibehörde Borken / Aaltense Musea „Markt 12“ - Büßink, Jochen (Westmünsterland. Jahrbuch des Kreises Borken, 2010)
Keywords: Aalten; Dinxperlo; EUREGIO (Körperschaft); Europäische Integration; Grenzgebiet; Museum; Polizei; Polizeidienststelle; Projekt; Schüler; Zweiter Weltkrieg

Grenzen verdwijnen. De gevolgen van de Europese eenwording - Janssen, Ben (Gelderland 1900–2000, 2006)
Keywords: Europäische Integration; Grenzgebiet; Provinz Geldern

Spheres of Transnationalism within the European Union. On Open Doors, Thresholds and Drawbridges along the Dutch–German Border - Strüver, Anke (Journal of Ethnic and Migration Studies, 2005)
Abstract: „This article addresses the European Union's claim to establish transnational spaces through co-operation across its internal borders. Focusing on the Dutch–German borderland as an example, people's practices towards this border and their perceptions of it are introduced. It is underscored that these practices are influenced by popular representations, which (re)produce bounded spaces and the barrier effect of the border, thus making it difficult to imagine a transnational space. This observation is complemented by the phenomenon that—due to a housing shortage in the Netherlands—Dutch people have recently begun to move to German places directly on the border, although they maintain their jobs in the Netherlands. Concentrating specifically on one of these German villages, Kranenburg, the emergence of a community of transmigrants is highlighted in order to reflect upon the question of whether this form of frequent short-distance border crossing fosters a European transnational sphere.“
Keywords: Europäische Integration; Grenzarbeitnehmer; Grenzgebiet; Kranenburg (Kleve); Sozialraum; Transnationalisierung

Fallstudien für deutsch-niederländische Grenzräume - Danielzyk, Rainer; Ernste, Huib; Jung, Hans-Ulrich (Entwicklung europäischer Grenzräume bei abnehmender Bedeutung nationaler Grenzen. Deutsch-dänische und deutsch-niederländische Grenzräume im europäischen Integrationsprozess, 2004)
Keywords: Deutschland; Europäische Integration

The Maas-Rhine Euroregion. A Laboratory for European Integration? - Knippenberg, Hans (Geopolitics, 2004)
„The transborder and trilingual Maas–Rhine Euroregion is often presented as a laboratory for European integration. The authorities in the region promote the image of a region that has ‘always’ been a unity, but which is divided by artificial boundaries – ‘scars of history’ – as a result of power politics. In this essay this image is confronted with the reality of the cross-border interactions and identities of the people involved. This confrontation leads to the conclusion that although there is political, economic and cultural cooperation in the region, the region is not at all politically, economically and culturally integrated. The national border as a physical barrier may have been removed, but the economic, social, juridical and cultural barriers are still there. The unification and integration of the citizens living in the region is being impeded by conflicting national systems of law and regulations, by communication and information media focused on national issues, by nationally oriented infrastructure, and especially by strongly different national cultures and identities. The consequences for European integration in general are analysed by comparing this regional integration with the national integration and nation-building policies of the past.“
Keywords: Euregio Maas-Rhein; Europäische Integration; Grenzüberschreitende Kooperation

Die Entwicklung in deutsch-dänischen und deutsch-niederländischen Grenzregionen vor dem Hintergrund ökonomischer Theorien - Lammers, Konrad (Entwicklung europäischer Grenzräume bei abnehmender Bedeutung nationaler Grenzen. Deutsch-dänische und deutsch-niederländische Grenzräume im europäischen Integrationsprozess, 2004)
Keywords: Deutschland; Dänemark; Europäische Integration

Significant insignificance. Boundaries in a borderless European Union. Deconstructing the Dutch–German transnational labour market - Strüver, Anke (Journal of Borderlands Studies, 2002)
Abstract: „This contribution elaborates on European Union (E.U.) geopolitical discourses, which attempt to overcome the ‘insignificance’ of state‐borders through the establishment of cross‐border regions. Drawing on the nonexisting Dutch‐German transnational labor market as an example, the observed ‘non‐practice’ of border crossing is introduced. ‘Significant boundaries’ and their meanings, on the other hand, are constructed by narratives and images that are not only representations, but also actively shape people's everyday life. The effects of these boundary narratives are analyzed in terms of ‘cognitive distance’, defined both as the creation of a barrier effect and the ignorance of what lies beyond, expressed as a boundary in people's minds.“
Keywords: Arbeitsmarkt; Europäische Integration; Grenzarbeitnehmer; Grenzgebiet; Grenzüberschreitende Kooperation

Von der internationalen zur transnationalen Politik. Dargestellt am Beispiel der europäischen (Kern-)Region Saar-Lor-Lux-Trier/Westpfalz ; Entwicklung eines (3+1)-Ebenen-Modells interregionaler Zusammenarbeit - Sinewe, Werner (Lang, 1998)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage/2006/01/01/file_465/1127453.pdf
Keywords: Europäische Integration; Grenzüberschreitende Kooperation; Regionalpolitik; Saar-Lor-Lux